Functional plasticity in the respiratory drive to thoracic motoneurons in the segment above a chronic lateral spinal cord lesion - Ford, T.W.; Anissimova, N.P.; Meehan, C.F.; Kirkwood, P.A. (American Physiological Society, 2015)
A previous neurophysiological investigation demonstrated an increase in functional projections of expiratory bulbospinal neurons (EBSNs) in the segment above a chronic lateral thoracic spinal cord lesion which severed their axons. We have now investigated how this plasticity might be manifested in thoracic motoneurons, by measuring their respiratory drive and the connections to them from individual EBSNs. In anesthetized cats, simultaneous recordings were made intracellularly from motoneurons in the segment above a left-side chronic (16 week) lesion of the spinal cord in the rostral part of T8, T9 or T10 and extracellularly from EBSNs in the right caudal medulla, antidromically excited from just above the lesion, but not from below. Spike-triggered averaging was used to measure the connections between pairs of EBSNs and motoneurons. Connections were found to have a very similar distribution to normal and were, if anything (non-significantly), weaker than normal, being present for 42/158 pairs, vs. 55/154 pairs in controls. The expiratory drive in expiratory motoneurons appeared stronger than in controls, but again not significantly so. Thus we conclude that new connections made by the EBSNs following these lesions were made to neurons other than alpha-motoneurons. However, a previously unidentified form of functional plasticity was seen, in that there was a significant increase in the excitation of motoneurons during post-inspiration, being manifest either in increased incidence of expiratory-decrementing respiratory drive potentials, or in an increased amplitude of the post-inspiratory depolarizing phase in inspiratory motoneurons. We suggest that this component arose from spinal cord interneurons.